KORELASI ANTARA TEMA TAHALUL DENGAN EVALUASINYA DALAM KONTEKS PEMBIMBINGAN HAJI DI JAWA TENGAH - Huda, Nurul (Nurani, 2016)
This article focused to explore Tahallul Theme in guidance of hajj konteks in Central Java province. Content analysis method used aims to describe the correspondence between variables and variable themes mengkolerasikan both the evaluation and contingency coefficient. Through computing reliability test questionnaire and test hypotheses, unknown numbers Kappa inter-rater reliability of 0.72, which means strong or substantial contingency and correlation coefficients (kk) of 0.89, which means strong. The results of computing the correlation of two variables showed the coefficient of contingency with a description of the index suitability theme per item matrix two variables and ditriangulasikan theme per item hadith thematic work Suhaib Abdul Jabbar adapted by item matrix with books guidance Rituals of Hajj MoRA, with an index of suitability Kappa at 0,41 which means enough. The results of calculations per item theme suitability computing two variables consisting of items MoRA as a reference thematic matrix and matrix item 73 rater of KBIH that produces its own rituals books, can be explained.ملخص: هذا البحث هو دراسة منهج تحليل المضمون الكمي. الطريقة المستخدمة تحليل أهداف المحتوى لوصف المراسلات بين المتغيرات والموضوعات كل من معامل التقييم والطوارئ. من خلال الحوسبة الموثوقية استبيان اختبار واختبار الفرضيات، أرقام مجهولة كابا بين التصنيفات موثوقية 0.72، مما يعني طوارئ قوي أو كبير ومعاملات الارتباط (ك ك) من 0.89، مما يعني قوية. وأظهرت نتائج حساب الارتباط بين متغيرين معامل طوارئ، مع وصف للموضوع مؤشر ملاءمة لكل بند مصفوفة اثنين من المتغيرات وموضوع في البند الحديث عمل مواضيعي صهيب عبد الجبار تكييفها حسب بند مصفوفة مع طقوس توجيه كتب الحج مورا، مع مؤشر ملاءمة كابا في 0، 41 مما يعني بما فيه الكفاية. نتائج عملية حسابية في الحوسبة ملاءمة موضوع البند اثنين من المتغيرات التي تتكون من عناصر مورا كمرجع مواضيعي المصفوفة والمصفوفة البند 73 من التصنيفات من KBIH التي تنتج الكتب الطقوس الخاصة به، ويمكن تفسير.